PENGEMBANGAN E-MODUL BERBASIS FLIP-BOOK TERINTEGRASI NILAI-NILAI KEISLAMAN PADA PEMBELAJARAN IPAS MATERI KERAJAAN ISLAM KELAS IV SD - Wina Humaira; Tursinawati; Intan Safiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the demands of the 21st century that encourage the use of technology in education and the need for learning innovations that are not only digital, but also shape the character of students through the integration of Islamic values, so that it includes the development of cognitive, spiritual, and moral aspects. The purpose of this study is to examine the process and results of the development of flip-book-based E-modules that integrate Islamic values in learning Islamic Kingdom materials for grade IV elementary school students who meet valid, practical, and effective criteria. This research uses the Research and Development (R&D) method with the ADDIE model which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The subjects of the study were students in grades IVa and IVb of SD Negeri 2 Mata Ie, with 16 students in the small-scale test and 30 students in the large-scale test. The instruments used were validation sheets by validators, student response questionnaires, and evaluation test questions. The data analysis technique used in this study uses descriptive qualitative analysis consisting of validity analysis, practicality analysis, and effectiveness analysis. The results of the study showed that the E-module developed met the criteria very valid with the validation results of material experts of 93.04% with the criterion of "Excellent" and the validation of media experts of 94% with the criterion of "Excellent". The e-module was also declared practical based on the student response questionnaire on the small-scale test of 94.19% with the criterion of "Excellent" and the wide scale of 96.07% with the criterion of "Excellent". In addition, the E-module is quite effective, as evidenced by 100% of students obtaining scores above the Minimum Completeness Criteria (KKM) in small-scale and large-scale trials.